Three Solutions Theorem for p-Laplacian Problems with a Singular Weight and Its Application - Yong-Hoon Lee; Seong-Uk Kim; Eun Kyoung Lee (Abstract and Applied Analysis)
We prove Amann type three solutions theorem for one dimensional p-Laplacian problems with a singular weight function. To prove this theorem, we define a strong upper and lower solutions and compute the Leray-Schauder degree on a newly established weighted solution space. As an application, we consider the combustion model and show the existence of three positive radial solutions on an exterior domain.